An Analysis of Accuracy in Translating News Item Text from Bahasa Indonesia to English Done by The Third Year English Department Students - Fuadi Imam; Rusdi Noor Rosa (Journal of English Language Teaching, 2023)
The accuracy in translation is one of important aspects in translation quality. Accuracy is a term used to determine whether the message in the source language or target languages is equivalent or not. This study aimed to find out the accuracy the third year English Department students at Universitas Negeri Padang translate news item texts from Bahasa Indonesia to English as well as to describe inversion and deviation of meaning. The sample of this research was 32 students from Translation class at English Department chosen by using cluster random sampling. The focus of this study was the students accuracy in translating news item text from Bahasa Indonesia to English and kinds of errors in students translation work. The data of this research were obtained from the result of translation test about translating news item from Bahasa Indonesia into English. The data were assessed by using a rubric of accuracy rating instrument. The result of the research showed that the average of students accuracy in translating news item text from Bahasa Indonesia to English was 21.4 which categorized into almost completely successful. Furthermore, the occurrence of errors in students translation work was categorized into two types, namely, inversion and deviation of meaning in which deviation of meaning became the highest percentage of error (97.3%).